2005
DOI: 10.1007/s11270-005-1248-z
|View full text |Cite
|
Sign up to set email alerts
|

Remediation Actions by a Risk Assessment Approach: A Case Study of Mercury Contamination

Abstract: Abstract. The risk assessment procedure for identifying the remediation actions which may be adopted at a mercury contaminated site, when the plants are upgraded in the future, is proposed. The potentially active exposure/migration pathways in the future arrangement of the area will be due to Hg contaminated subsoil as a primary source (vapor inhalation and groundwater leaching) and to groundwater as a possible secondary source (transport to the point of compliance).The data of mercury concentration in the soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Saponaro et al, 2005 study concluded that even the most abundant mercury species in soil are poorly leachable under the site-specific environmental conditions. In general, human health and environmental risk assessments for metals are difficult to estimate because environmental behavior and toxicity depend on metal chemical forms and soil properties, such as pH value and redox potential, and these properties greatly vary in the environment.…”
Section: Risk Assessment General Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Saponaro et al, 2005 study concluded that even the most abundant mercury species in soil are poorly leachable under the site-specific environmental conditions. In general, human health and environmental risk assessments for metals are difficult to estimate because environmental behavior and toxicity depend on metal chemical forms and soil properties, such as pH value and redox potential, and these properties greatly vary in the environment.…”
Section: Risk Assessment General Conceptsmentioning
confidence: 99%
“…Furthermore, the study concluded that given the serious risks posed by methyl mercury to mink and kingfishers, the next step is to evaluate possible remedial options that could be used to reduce risks to acceptable levels. Saponaro et al, 2005, developed a risk assessment procedure to identify the remediation actions that may be adopted at a mercury-contaminated site. Analytical and numerical fate and transport modeling tools were used to locate digging zones in contaminated subsoil, to reduce the possible groundwater contaminant loading, and to avoid exceeding concentration limits.…”
Section: Risk Assessment General Conceptsmentioning
confidence: 99%